Low-carbon grouting material for blocking small karst cavity of karst stratum, preparation method, application and construction method
By using the A, B, and C component ratios of low-carbon grouting materials and the construction method, the problems of high carbon emissions and insufficient stability of traditional cement grouting materials in karst formations were solved, achieving efficient and long-term cavity sealing effects.
Patent Information
- Application Number
- CN202511687584.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-18
- Publication Date
- 2026-01-13
AI Technical Summary
Traditional cement grouting materials suffer from high carbon emissions, insufficient stability and durability when sealing small cavities in karst formations, making them difficult to effectively seal in environments rich in groundwater for extended periods.
A three-component low-carbon grouting material (A, B, and C) is used. Component A is a mixture of cement, fly ash, and blast furnace slag; component B is a water glass solution; and component C is a waterproofing material composed of alkylamine-modified natural mordenite and microsilica powder. The sealing is achieved through reasonable proportioning and construction methods.
It significantly reduces carbon emissions, improves the density and impermeability of the grout, ensures long-term stable sealing effect, has good volume stability and crack resistance, and meets the construction needs of complex karst strata.
Smart Images

Figure CN121318320A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of tunnel engineering grouting technology, specifically a low-carbon grouting material, preparation method, application, and construction method for sealing small cavities in karst formations. Background Technology
[0002] As tunnel construction in my country shifts to the geologically complex and varied western regions, karst formations are becoming increasingly common in tunnel engineering. Karst formations possess unique landforms, hydrological systems, and underground spatial structures. Due to dissolution, cavities of varying sizes are prevalent within karst formations. The presence of these cavities can lead to instability in underground engineering projects and may be connected to groundwater systems. If not effectively sealed, these cavities could cause groundwater pollution and resource waste. Therefore, for safety and environmental reasons, effective sealing of cavities within the scope of underground engineering projects is essential. Currently, traditional grouting sealing methods primarily use cement and other materials to prepare grout for filling. However, the materials used in traditional sealing methods have a significant environmental impact, generating substantial carbon emissions during production and use, with the large-scale use of cement being a major source of these emissions. Furthermore, the stability and durability of traditional sealing materials are questionable, making it difficult to guarantee long-term sealing effectiveness in karst formations rich in groundwater. In the face of these problems, it is urgent to develop low-carbon and durable sealing technologies. In recent years, the emergence of various new materials has provided new ideas and methods for sealing small cavities in karst formations.
[0003] Therefore, the present invention aims to develop a low-carbon grouting material preparation and application technology for small cavities in karst formations. Through reasonable proportioning and construction methods, it can achieve efficient sealing and reinforcement of small cavities, thereby making a beneficial contribution to the safety and stability of underground engineering, the protection of groundwater resources, and the maintenance of the ecological environment. Summary of the Invention
[0004] To address the aforementioned problems, this invention provides a low-carbon grouting material, its preparation method, its application, and its construction method for sealing small cavities in karst formations.
[0005] The present invention adopts the following technical solution: a low-carbon grouting material for sealing small cavities in karst formations, which is composed of three components A, B and C mixed in a volume ratio of 1:0.4:0.05; Component A is the base material of cement slurry, which is made by mixing cement, fly ash and blast furnace slag in a mass ratio of 1:2:0.75 and controlling the water-cement ratio to be 0.4:1. Component B is a water glass solution, wherein water accounts for 25% by mass; Component C is a waterproof material, which is made by combining natural mordenite with microsilica powder after surface modification with alkylamine, and then adding polyacrylamide additives.
[0006] In some embodiments, the alkylamine surface modification treatment includes: placing natural mordenite in a 1% to 3% alkylamine salt solution, stirring at 50 to 70°C for 2 to 4 hours, and obtaining the product after filtration, washing, and drying.
[0007] In some embodiments, the modulus of water glass in component B is 2.4 to 2.8.
[0008] In some embodiments, in the C component waterproof material, the mass ratio of modified natural mordenite to microsilica is 1:0.1.
[0009] In some embodiments, the polyacrylamide is a nonionic polyacrylamide with a molecular weight of 8 million to 12 million, and its addition amount is 0.5% to 1.5% of the total mass of modified natural mordenite zeolite and microsilica powder.
[0010] A method for preparing a low-carbon grouting material includes the following steps: S1: After grinding and sieving the blast furnace slag, it is dry-mixed with cement and fly ash, and then water is added and stirred to form a cement slurry of component A. S2: Mix water glass with water to prepare component B water glass solution; S3: Natural mordenite is surface-modified with alkylamine, then mixed with silica powder, polyacrylamide additives and water are added and stirred to make component C waterproof material; S4: Mix the components A, B and C according to the volume ratio and stir evenly to obtain the low-carbon grouting material.
[0011] In some embodiments, in step S4, component A and component B are mixed first, and then component C is added.
[0012] Application of a low-carbon grouting material in sealing small cavities in karst formations.
[0013] A construction method for sealing small cavities in karst formations, using low-carbon grouting materials, includes the following steps: P1: Probe and clean the cavity; P2: Drill holes and install grouting pipes; P3: The low-carbon grouting material is injected into the grouting cavity at a pressure of 0.5~1.0MPa using a grouting pump; P4: After the grouting material has cured, conduct acceptance testing.
[0014] Compared with the prior art, the present invention has the following beneficial effects: This invention significantly reduces carbon emissions at the source by extensively utilizing industrial byproducts such as fly ash and blast furnace slag to replace traditional cement, achieving green recycling of resources. The innovative introduction of natural mordenite-based waterproofing material works synergistically with the system, significantly enhancing the density and impermeability of the slurry, effectively resisting groundwater erosion and ensuring long-term stable sealing effects. At the same time, the material possesses excellent volume stability, crack resistance, and self-healing ability, avoiding the problem of drying shrinkage cracks. Its excellent workability and pumpability also ensure construction adaptability and filling fullness in complex karst strata, providing a comprehensive solution for the safe, efficient, and permanent sealing of small cavities in tunnel engineering. Attached Figure Description
[0015] Figure 1 Flowchart for the preparation of low-carbon grouting materials; Figure 2 Low-carbon grouting construction process for sealing small cavities in karst formations. Detailed Implementation
[0016] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are some embodiments of the present invention, but not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0017] The unique characteristics of karst formations lie in the fact that groundwater dissolves soluble rocks such as limestone through erosion, forming irregular caves and cavities. These erosion features present challenges in underground engineering projects involving cave treatment and water control. Currently, traditional cement grouting materials and techniques suffer from inconsistent curing effects within cavities due to groundwater flow and erosion, leading to unstable curing results and durability. Furthermore, the extensive use of cement in current grouting materials results in significant carbon emissions. Additionally, the cement grout generates substantial heat of hydration during curing, and excessive water evaporation can cause the final grout to be loose or even cracked, severely impacting grouting quality. This invention, based on the hydrogeological characteristics of karst formations, addresses the filling and remediation of small cavities encountered during construction. By replacing most of the cement with renewable materials and introducing a waterproof material made from natural mordenite and microspheres, the impermeability, density, and crack resistance of the grout are enhanced. This also promotes self-healing to some extent, improving long-term crack resistance and volume stability.
[0018] Specific implementation examples are as follows: Example 1: Preparation and Construction of Low-Carbon Grouting Materials: A low-carbon grouting material for sealing small cavities in karst formations is composed of three components, A, B, and C, mixed in a volume ratio of 1:0.4:0.05. Component A is the base material of cement slurry, which is made by mixing cement, fly ash and blast furnace slag in a mass ratio of 1:2:0.75 and controlling the water-cement ratio to be 0.4:1. Component B is a water glass solution, wherein water accounts for 25% by mass; Component C is a waterproof material, which is made by combining natural mordenite with microsilica powder after surface modification with alkylamine, and then adding polyacrylamide additives.
[0019] The surface modification treatment of the alkylamine includes: placing natural mordenite in a 1% to 3% alkylamine salt solution, stirring at 50 to 70°C for 2 to 4 hours, and obtaining the product after filtration, washing, and drying.
[0020] Polyacrylamide is a non-ionic polyacrylamide with a molecular weight of 8 million to 12 million. Its addition amount is 0.5% to 1.5% of the total mass of modified natural mordenite zeolite and microsilica powder.
[0021] like Figure 1 As shown, the preparation method is as follows: S1: After grinding and sieving the blast furnace slag, it is dry-mixed with cement and fly ash, and then water is added and stirred to form a cement slurry of component A. Material preparation: Prepare the required raw materials, including silicate cement, fly ash, water glass, and blast furnace slag as grouting base materials, and natural mordenite zeolite, microsilica powder, alkylamine, and polyacrylamide (PAM) additives to make waterproof materials. Calculate the weight of each raw material required according to the proportions.
[0022] Dry mixing of slurry base material: After grinding and sieving the blast furnace slag, the required weight of silicate cement, fly ash and blast furnace slag are dry mixed to ensure uniform mixing of powder.
[0023] S2: Mix water glass with water to prepare component B water glass solution; Preparation of water glass: To prepare a water glass solution, mix an appropriate amount of water glass with an appropriate amount of water. The modulus of the water glass should be 2.4–2.8, and the water content is typically 25%, but this can be adjusted according to specific requirements. Stir until homogeneous to form a water glass solution.
[0024] S3: Natural mordenite is surface-modified with alkylamine, then mixed with silica powder, polyacrylamide additives and water are added and stirred to make component C waterproof material; A measured amount of natural mordenite zeolite is placed in a container, and alkylamine modifier is gradually added while stirring to ensure full contact between the mordenite zeolite and the modifier. Stirring continues to allow the alkylamine to adsorb and modify on the surface of the mordenite zeolite. After alkylamine modification is complete, the mordenite zeolite is removed and dried. The modified mordenite zeolite and silica powder are mixed in a 1:0.1 ratio in a container, and an appropriate amount of water is added and stirred to fully disperse the base material in the water. Polyacrylamide (PAM) additive is gradually added, and stirring continues to improve the viscosity and stability of the waterproof material. Stirring continues until all components of the waterproof material are fully mixed and homogeneous, forming a stable waterproof material.
[0025] S4: Mix the components A, B and C according to the volume ratio and stir evenly to obtain the low-carbon grouting material.
[0026] Mix the prepared dry materials with water, maintaining a water-to-cement ratio of 0.4:1 to form a cement-based grout. Pour the prepared water glass solution into the cement-based grout, with a volume ratio of cement-based grout to water glass of 1:0.3 to 1:0.6. While stirring, gradually pour the waterproofing material suspension into the mixture, continuing to stir to ensure all materials are thoroughly and evenly mixed. The final product is a low-carbon grouting material for sealing small cavities in karst formations.
[0027] A construction method for sealing small cavities in karst formations, using low-carbon grouting materials, includes the following steps: P1: Probe and clean the cavity; This mainly includes conducting advance surveys of the construction area to determine the location, size, and distribution of the cavities. It also involves cleaning the interior of the cavities of debris, soil, and water, and performing surface treatment to improve the adhesion of the sealing grouting material.
[0028] P2: Drill holes and install grouting pipes; After determining the location and size of the grouting hole, the steel pipe for grouting is fabricated. A rock drill or coal drill is used to drill the hole, with the hole diameter being more than 20mm larger than the designed guide pipe diameter. After the hole is formed, the grouting pipe is inserted into the hole.
[0029] P3: The low-carbon grouting material is injected into the grouting cavity at a pressure of 0.5~1.0MPa using a grouting pump; Use a grouting pump to inject the prepared grouting liquid into the small cavity through the grouting pipe. Select a grouting pressure of 0.5~1.0MPa and inject the grouting liquid gradually to ensure that the grouting liquid fully diffuses and fills the entire cavity.
[0030] P4: After the grouting material has cured, conduct acceptance testing.
[0031] The grouting material is allowed to solidify and harden within the small cavity, forming a robust sealing layer. Finally, acceptance testing is conducted to check the strength, density, and waterproofing performance of the sealing layer. If necessary, the sealing layer can be further treated, such as by applying waterproof or anti-corrosion coatings, to further improve its durability.
[0032] Traditional cement grouting materials typically use a high proportion of cement to achieve the required strength and consistency of the grout. However, excessive cement increases carbon emissions and resource consumption. Firstly, this invention uses renewable resources such as fly ash and blast furnace slag in the grouting base material to replace most of the cement, fully utilizing these industrial byproducts, reducing the demand for raw resources, improving resource utilization efficiency, and minimizing resource consumption and carbon emissions during the production of grouting raw materials.
[0033] Furthermore, the introduction of waterproofing materials has reduced cement usage. Mordenite, a natural mineral and a low-carbon resource, is used in grouting as a waterproofing material. This allows for reduced cement usage while maintaining the required grout performance, thus lowering carbon emissions and environmental impact. Mordenite is a microcrystalline structure composed of silicate minerals, primarily consisting of silicon, aluminum, calcium, and sodium. Its reaction with cement is mainly described by the following equation: Si3+-O-Si3++6OH-→2[SiO(OH)3]- Si3+-O-Al3++7OH-→[SiO(OH)3]-+[Al(OH)4]- The process involves the combination of active silicon, aluminum, and Ca2+ in cement to form hydrated calcium silicate (CSH) and calcium aluminate complex salts. This increases the cement hardening gel products, improves the bonding between aggregates and cementitious materials, increases the density of the cement paste, enhances strength and volume stability, and thus improves impermeability, making it highly suitable for sealing groundwater in karst formations. Furthermore, it possesses properties such as reducing drying shrinkage, inhibiting the rate of heat release from cement hydration, micro-expansion, and self-healing. While maintaining the same strength, it can significantly reduce the amount of cement used, resulting in a significant improvement in the performance and emission reduction effect of grouting materials.
[0034] Performance comparison test: To verify the performance advantages of the low-carbon grouting material of this invention, a comparative experiment with traditional cement grouting materials was conducted.
[0035] Control group: Pure cement grouting material, PO 42.5 cement paste with a water-cement ratio of 0.5:1 was used.
[0036] Example: The low-carbon grouting material prepared in Example 1 was used.
[0037] Specimens were prepared and tested in accordance with relevant standards such as "Test Method for Strength of Cement Mortar (ISO Method)" (GB / T 17671-2021) and "Standard for Test Methods for Long-Term Performance and Durability of Ordinary Concrete" (GB / T 50082-2009). The results are shown in the table below.
[0038] Table 1: Comparison of the performance of different grouting materials Analysis of experimental results: Setting time: The initial and final setting times of the material of this invention are significantly shorter than those of traditional cement grout. This is due to the setting-promoting effect of water glass, which enables it to solidify rapidly, making it suitable for sealing cavities containing flowing water.
[0039] Compressive strength: The 7-day strength of the material of this invention is slightly lower than that of traditional cement grout, but the 28-day strength surpasses it. This indicates that the pozzolanic effect of fly ash and blast furnace slag is fully utilized in the later stages, and the generated CSH gel and other products continuously fill the pores, resulting in a sustained increase in strength in the later stages, meeting the long-term load-bearing requirements.
[0040] Impermeability: The impermeability of the material of this invention is far superior to that of traditional cement grout. This is mainly due to the role of component C waterproofing material: modified mordenite and microsilica fill the tiny pores inside the grout, while their active ingredients participate in the secondary hydration reaction to generate insoluble gel, which greatly improves the density of the grout, thereby effectively resisting the erosion of groundwater.
[0041] Drying shrinkage rate: The drying shrinkage rate of the material of this invention is much lower than that of traditional cement grout. Siliceous zeolite has micro-expansion properties, which can compensate for the chemical and drying shrinkage of the grout during the hardening process, significantly improving the volume stability of the grout and effectively avoiding the sealing failure problem caused by drying shrinkage cracking.
[0042] In summary, the low-carbon grouting material provided by this invention, while making extensive use of industrial solid waste and achieving low-carbon and environmentally friendly practices, has significantly improved comprehensive performance (especially impermeability and volume stability) compared to traditional cement grouting materials, and can better meet the stringent requirements of small-scale karst cavity sealing projects.
[0043] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A low-carbon grouting material for sealing small cavities in karst formations, characterized in that, It is composed of three components, A, B, and C, mixed in a volume ratio of 1:0.4:0.05; Component A is the base material of cement slurry, which is made by mixing cement, fly ash and blast furnace slag in a mass ratio of 1:2:0.75 and controlling the water-cement ratio to be 0.4:
1. Component B is a water glass solution, wherein water accounts for 25% by mass; Component C is a waterproof material, which is made by combining natural mordenite with microsilica powder after surface modification with alkylamine, and then adding polyacrylamide additives.
2. The low-carbon grouting material according to claim 1, characterized in that, The surface modification treatment of the alkylamine includes: placing natural mordenite in a 1% to 3% alkylamine salt solution, stirring at 50 to 70°C for 2 to 4 hours, and obtaining the product after filtration, washing, and drying.
3. The low-carbon grouting material according to claim 1, characterized in that, The modulus of the water glass in component B is 2.4 to 2.
8.
4. The low-carbon grouting material according to claim 1, characterized in that, In the C-component waterproof material, the mass ratio of modified natural mordenite to microsilica is 1:0.
1.
5. The low-carbon grouting material according to claim 1, characterized in that, The polyacrylamide is a nonionic polyacrylamide with a molecular weight of 8 million to 12 million, and its addition amount is 0.5% to 1.5% of the total mass of modified natural mordenite zeolite and microsilica powder.
6. A method for preparing a low-carbon grouting material as described in any one of claims 1 to 5, characterized in that, Includes the following steps: S1: After grinding and sieving the blast furnace slag, it is dry-mixed with cement and fly ash, and then water is added and stirred to form a cement slurry of component A. S2: Mix water glass with water to prepare component B water glass solution; S3: Natural mordenite is surface-modified with alkylamine, then mixed with silica powder, polyacrylamide additives and water are added and stirred to make component C waterproof material; S4: Mix the components A, B and C according to the volume ratio and stir evenly to obtain the low-carbon grouting material.
7. The preparation method according to claim 6, characterized in that, In step S4, component A and component B are mixed first, and then component C is added.
8. The application of a low-carbon grouting material as described in any one of claims 1 to 5 in sealing small cavities in karst formations.
9. A construction method for sealing small cavities in karst formations, characterized in that, The method of using the low-carbon grouting material as described in any one of claims 1 to 5 includes the following steps: P1: Probe and clean the cavity; P2: Drill holes and install grouting pipes; P3: The low-carbon grouting material is injected into the grouting cavity at a pressure of 0.5~1.0MPa using a grouting pump; P4: After the grouting material has cured, conduct acceptance testing.